What Can We Still Learn from Brain Autopsies in COVID-19? - Solomon, Isaac H.; Singh, Arjun; Folkerth, Rebecca D.; Mukerji, Shibani S. (Seminars in Neurology, 2023)
Neuropathological findings have been published from ∼900 patients who died with or from severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infections, representing less than 0.01% of the close to 6.4 million deaths reported to the World Health Organization 2 years into the coronavirus disease 2019 (COVID-19) pandemic. In this review, we extend our prior work summarizing COVID-19 neuropathology by including information on published autopsies up to June 2022, and neuropathological studies in children, COVID-19 variants, secondary brain infections, ex vivo brain imaging, and autopsies performed in countries outside of the United States or Europe. We also summarize research studies that investigate mechanisms of neuropathogenesis in nonhuman primates and other models. While a pattern of cerebrovascular pathology and microglial-predominant inflammation remains the primary COVID-19-associated neuropathological finding, there is no singular understanding of the mechanisms that underlie neurological symptoms in acute COVID-19 or the post-acute COVID-19 condition. Thus, it is paramount that we incorporate microscopic and molecular findings from brain tissue into what we know about the clinical disease so that we attain best practice guidance and direct research priorities for the study of the neurological morbidity of COVID-19.
Keywords: COVID-19; severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2); brain autopsies; neuropathological findings; children with COVID-19; Rhino-orbito-cerebral mucormycosis COVID-19 Neuropathogenesis